Short Communication: Identification of culturable marine fungi and bacteria from coastal region in Brunei Darussalam: Identification of culturable marine microbes. - Hussein Taha; Pooja Shivanand; Mohamad Abdul Azim Zainudin; Nurul Azirah Hadanan (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Taha H, Shivanand P, Zainudin MAA, Hadanan NA. 2021. Short Communication: Identification of culturable marine fungi and bacteria from coastal region in Brunei Darussalam. Biodiversitas 22: 1326-1331. Microbial diversity in Brunei Darussalam located on northwest coast of Borneo is not well explored. This study aimed to isolate and identify culturable marine fungi and bacteria from coastal regions. Microbial identification was carried out via DNA barcoding using rRNA-ITS marker for fungi and 16S rRNA marker for bacteria. Nine marine fungal isolates were identified to five genera as Aspergillus, Penicillium, Phialemoniopsis, Purpureocillium and Trametes. However, only one genus, Pseudoalteromonas was identified from ten marine bacterial isolates with at least three different Pseudoalteromonas species expected from the isolation. This study provided an insight into the diversity of culturable marine microbes from a coastal ecosystem. As the microbes were found culturable and can easily grow under saline conditions, they are potential of considerable biotechnological interest.